Теоретико-прикладні аспекти реструктуризації національної економіки України - Halasiuk, Viktor (Dr. Viktor Koval, 2019)
Introduction. The article deals with problems and consequences of the Ukrainian economy deindustrialization under the neoliberal paradigm dominance in government's economic policy. The problems of deindustrialization in transition economies during the period of postindustrial transformation in developed countries and the neoliberal economic thought dominance has so far been overlooked. The subject-matter of the study is structural shifts caused by deindustrialization and diversification of the economy. The methodological principles of research involve joint application of a set of well-known common scientific methods as well as special research methods in economics, such as retrospective analysis method to investigate the origin of modern neoliberal economic doctrines. Aim and tasks. The purpose of the article is to distinguish the fundamental differences in structural changes in the economy of Ukraine and developed countries and to identify key areas for restructuring the domestic economy on the basis of modernization and reindustrialization policy. Results. The fundamental differences between dramatic reduction of the industrial sector share in the Ukrainian economy and economy diversification with a relative decrease in the share of industry that occurs in mature economic systems under transition to the postindustrial stage of development are revealed. It’s proved that formal signs of a transition to a postindustrial society may reflect diametrically opposed trends of economic development. A critical analysis of the theoretical postulates of economic thought that underlies leading international organizations’ cooperation with individual countries is conducted. It’s argued that neoliberal economic paradigm relies on abstract, sterile, and unfeasible hypotheses based on ideology, not the experience of successful structural transformations. Key areas of Ukraine's economic policy transformation include a set of tools of budget, infrastructure, tax, customs and foreign trade policies to ensure structural changes in output and export. It’s argued that such measures, as introducing a local component criterion in public procurements, free connection of industrial objects to engineering networks, tax incentives for industrial park residents, barriers to raw materials exports, revision of Ukraine’s obligations under WTO, launching of an export-credit agency, deploying a network of official trade missions in key partner countries, etc., will trigger reindustrialization of Ukrainian economy. Conclusions. Implementation of a full-fledged industrial policy in developing countries is hampered by the rule of neo-liberal economic ideology, which denies the possibility of effective state governance of structural changes in the national economy. The article puts forward a critical view on the mainstream economic ideology and discusses its destructive impact on the Ukrainian economy that is worth to be introduced in masters’ graduation programs in economics. Implementation of author’s recommendations on reforming governmental economic and industrial policy is a basis for launching reindustrialization processes in the Ukrainian economy.